Ultrasensitive Detection of SARS-CoV‑2 Antibody by Graphene Field-Effect Transistors - Kang, Hua; Wang, Xuejun; Guo, Mingquan; Dai, Changhao; Chen, Renzhong; Yang, Lei; Wu, Yanling; Ying, Tianlei; Zhu, Zhaoqin; Wei, Dapeng; Liu, Yunqi; Wei, Dacheng (Nano letters, 2021)
The fast spread of SARS-CoV-2 has severely threatened the public health. Establishing a sensitive method for SARS-CoV-2 detection is of great significance to contain the worldwide pandemic. Here, we develop a graphene field-effect transistor (g-FET) biosensor and realize ultrasensitive SARS-CoV-2 antibody detection with a limit of detection (LoD) down to 10–18 M (equivalent to 10–16 g mL–1) level. The g-FETs are modified with spike S1 proteins, and the SARS-CoV-2 antibody biorecognition events occur in the vicinity of the graphene surface, yielding an LoD of ∼150 antibodies in 100 μL full serum, which is the lowest LoD value of antibody detection. The diagnoses time is down to 2 min for detecting clinical serum samples. As such, the g-FETs leverage rapid and precise SARS-CoV-2 screening and also hold great promise in prevention and control of other epidemic outbreaks in the future.